Brevianamide F Exerts Antithrombotic Effects by Modulating the MAPK Signaling Pathway and Coagulation Cascade - Huiwen Zhang; Chen Sun; Qing Xia; Peihai Li; Kechun Liu; Yun Zhang (Marine Drugs, 2024)
Existing antithrombotic drugs have side effects such as bleeding, and there is an urgent need to discover antithrombotic drugs with better efficacy and fewer side effects. In this study, a zebrafish thrombosis model was used to evaluate the antithrombotic activity and mechanism of Brevianamide F, a deep-sea natural product, with transcriptome sequencing analysis, RT-qPCR analysis, and molecular docking. The results revealed that Brevianamide F significantly attenuated the degree of platelet aggregation in the thrombus model zebrafish, leading to an increase in the number of circulating platelets, an augmentation in the return of blood to the heart, an elevated heart rate, and a significant restoration of caudal blood flow velocity. Transcriptome sequencing and RT-qPCR validation revealed that Brevianamide F may exert antithrombotic effects through the modulation of the MAPK signaling pathway and the coagulation cascade reaction. Molecular docking analysis further confirmed this result. This study provides a reference for the development of therapeutic drugs for thrombosis.